An evaluation on potential anti-oxidant and anti-inflammatory effects of Crocin - Bastani, Sepideh (2022)
Crocin, an active ingredient derived from saffron, is one of the herbal components that has recently been considered by researchers. Crocin has been shown to have many anti-inflammatory and antioxidant properties, and therefore can be used to treat various diseases. It has been shown that Crocin has a positive effect on the prevention and treatment of cardiovascular disease, cancer, diabetes, and kidney disease. In addition, the role of this substance in COVID-19 pandemic has been identified. In this review article, we tried to have a comprehensive review of the antioxidant and anti-inflammatory effects of Crocin in different diseases and different tissues. In conclusion, Crocin may be helpful in pathological conditions that are associated with inflammation and oxidative stress.